Assessment of the Perennial Floods Affecting Residential Areas Along River Tille, Katsina Metropolitan, Katsina State, Nigeria - Ladan, Suleiman Iguda; Rilwanu, Tasi’u Yalwa (MO.RI Publishing, 2024)
Flooding constitutes a significant environmental challenge across Nigeria, recurring annually and notably affecting residential zones situated adjacent to streams, rivers, and Fadama areas. This study evaluates the perennial floods impacting residential locales along River Tille in Katsina Metropolitan, Katsina State, Nigeria. The research methodology encompassed field visits to the river-adjacent residential areas over a three-year span (2020-2022) and the dissemination of semi-structured questionnaires to ten respondents from six residential areas along the river. Findings indicate that the floods, attributed to factors such as heavy rainfall, proximal housing construction, the infilling of Maliyau pond, and inappropriate waste disposal, recur yearly. These floods have led to the loss of lives, property damage, and structural collapses. While local community initiatives have sought to mitigate these impacts, success has been limited. In response, the State Government, in collaboration with the World Bank in August 2020, initiated a flood control project, which commenced in September 2020 and concluded in 2021. Observations in 2022 revealed substantial flood management improvements, although certain project aspects remain unaddressed by the contractors. Further actions are recommended to ensure the project's full efficacy in managing the perennial floods and minimizing adverse effects on the community. This research is significant, offering detailed insights into the persistent flood issues in metropolitan river areas and assessing a government-executed flood control initiative.